A method of technical diagnostics for offshore structures - Son, Do (Vietnam Journal of Mechanics, 1994)
This paper describes the results of measurements and analysis of the parameters, characterizing technical state of offshore platforms in Vietnam Sea. Based on decreasing in time material characteristics because of corrosion and local destruction assessment on residual life time of platforms is given and variants for its repair are recommended. The results allowed to confirm advantage of proposed technical diagnostic method in comparison with others and have been used for oil and gas platform of Joint Venture "Vietsovpetro" in South Vietnam.